The Impact of Laws and Regulations on Micro and Small Enterprises in Niger and Swaziland - Joumard, Isabelle (OECD Development Centre Working Papers, 1992)
This Technical Paper presents the results of research on the impact of taxation and other regulations on micro and small enterprises (MSEs) in two countries of sub-Saharan Africa. The fiscal and other regulations of the countries studied - Niger and Swaziland - and their administrative systems are quite different. Based on approximately similar samples of enterprises from the two countries, this study estimated and compared the level of compliance with these different legal requirements, and also ascertained their consequences for the functioning and growth of these enterprises. The research revealed that the MSEs of the two countries do not comply with all the applicable regulations. The level of compliance itself depended more on the type of regulation and characteristics of the MSEs studied than on the country. It appears that the proportion of MSEs that are registered was nearly identical in the two countries, while differences depend primarily on location (rural versus urban) ...